Measuring The Impact of Socio-Technical Congruence in a Different Types of Software Life Cycle (Sains Humanika, 2017)
Measuring developer coordination is a fundamental challenge and complex task in software development organizations. One way used to conceptualize and measure developer coordination is known as 'Socio-Technical Congruence (STC)', which is fit between the coordination requirements established by the dependencies among tasks and the actual coordination activities carried out by the developers. However, STC has not been widely accepted as a broad theory. This is for the reason that, STC is relatively new, and there are many fundamental questions that need to be addressed and understood. This research intend to construct a model of the relationship between STC and project performance in the different types of software development lifecycle. The model constructed can be used to provide additional evidence to the body of knowledge, which will further strengthen the STC theory. Therefore, we outline research questions, the proposed method used to conduct the research, potential contributions and the expected results of the research.
Keywords: Coordination; socio-technical congruence; software development; actual coordination; coordination requirement